2015
DOI: 10.1039/c5tb02125a
|View full text |Cite
|
Sign up to set email alerts
|

Conductive surfaces with dynamic switching in response to temperature and salt

Abstract: This work demonstrates polymer brushes grafted from conductive polymer films which display dynamic surface switching dependent on salt, temperature and electrode potential. The electroactivity presented by the conductive polymer and the responsiveness of the grafted brushes leads to an interface with multiple control parameters. Here, we demonstrate this concept by grafting of uncharged brushes of poly(ethylene glycol)methyl ether methacrylates from conducting polymer poly(3,4-ethylenedioxythiophene) (PEDOT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
5
35
0
Order By: Relevance
“…42,43 The decrease in swollen thickness was more pronounced for NaCl, as expected from the reduced kosmotropic character of this electrolyte compared to Na 2 SO 4 . 47,74 We noted however that although similar swelling trends were observed for thicker PMETAC brushes (30 nm dry thickness), no marked salting out was observed in the range of concentrations tested ( Figure S3). Hence, the effect of ionic strength on the swelling of thicker PMETAC brushes was weaker (30 nm, Figure S3), perhaps indicating that only part of the brush (e.g., the upper brush compartment) directly responds to electrostatic shielding in our experiments.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…42,43 The decrease in swollen thickness was more pronounced for NaCl, as expected from the reduced kosmotropic character of this electrolyte compared to Na 2 SO 4 . 47,74 We noted however that although similar swelling trends were observed for thicker PMETAC brushes (30 nm dry thickness), no marked salting out was observed in the range of concentrations tested ( Figure S3). Hence, the effect of ionic strength on the swelling of thicker PMETAC brushes was weaker (30 nm, Figure S3), perhaps indicating that only part of the brush (e.g., the upper brush compartment) directly responds to electrostatic shielding in our experiments.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…The swelling behaviour of PDMAEMA and POEGMA brushes was previously studied by ellipsometry and reported by our group as well as others. 22,54 Fourier Transform Infrared-Attenuated Total Reflectance Spectroscopy (ATR-FTIR) was carried out using a Bruker Tensor 27 with an MCT detector (liquid N 2 cooled). Spectra were acquired at a resolution of 4 cm À1 with a total of 256 scans per run.…”
Section: Polymer Brush Synthesis On Planar Silicon Substratesmentioning
confidence: 99%
“…Furthermore, the morphology and mechanics of these interfaces can be regulated via the control of brush grafting density, thickness, swelling and conformation. 19,20 The wealth of monomers that can be incorporated in polymer brushes has enabled a wide range of properties for these coatings, including protein resistance, 21 thermoresponsiveness, 22,23 electrolyte responsiveness 24,25 and bacterial resistance. 26,27 In addition, brushes can be readily grown from a wide range of substrates, making these coatings attractive for a range of biomedical applications from implant design 28 to gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Travas‐Sejdic and coworkers demonstrated that uncharged brushes of poly(ethylene glycol)methyl ether methacrylates grafted from conducting polymer PEDOT (poly(BrEDOT)‐g‐poly(PEGMMA‐co‐DEGMMA) (Fig. ) can create temperature and salt‐induced switch of brush conformations with electroactive properties exerted by PEDOT . These polymers provided protein resistance even after repeated brush collapse/swelling cycles.…”
Section: Biomedical Applicationsmentioning
confidence: 99%